Management of Feeding Plates in Patients with Down Syndrome - Fuad Dirja; Iwan Ahmad Musnamirwan (Riviera Publishing, 2025)
Down Syndrome (DS) is a genetic disorder characterized by intellectual and physical developmental delays, often accompanied by craniofacial anomalies such as cleft lip and palate (CLP). These structural abnormalities impair feeding, swallowing, and oral functions, leading to nutritional deficiencies and growth challenges. This study explores the use of a feeding plate as a non-surgical intervention to improve feeding efficiency in DS patients with CLP. The research aims to evaluate the effectiveness of feeding plates in enhancing nutritional intake, stabilizing tongue position, and supporting craniofacial development. A case study was conducted on a 2-day-old male DS patient with palatoschisis. The feeding plate was fabricated under inhalation sedation, with impressions taken using putty material. The device was inserted and adjusted to ensure comfort and functionality. Parental education on usage and hygiene was emphasized. Findings revealed significant improvements in feeding efficiency, with the patient’s weight increasing from 3 kg to 5.5 kg over three months. The feeding plate also reduced nasal regurgitation and aspiration risks while providing psychological relief to caregivers. Early intervention with feeding plates was shown to be crucial for preoperative preparation and overall quality of life. The study underscores the importance of multidisciplinary care and early prosthetic intervention in DS patients with CLP. Feeding plates serve as a transitional tool, bridging the gap until surgical correction, and highlight the need for tailored, family-centered approaches in managing syndromic craniofacial anomalies.